The Effect of Liquidity, Profitability, and Solvency on Dividend Policy in Mining Companies Listed on the Indonesia Stock Exchange - Muhammad Rajali; Noni Ardian; Hernawaty (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The development of the iron and steel sub-sector mining industry in Indonesia has shown significant growth in recent years. This sector has a strategic role in supporting national infrastructure development and contributing to state revenue. The purpose of this study is to analyze the effect of liquidity, profitability, and solvency on dividend policy in iron and steel sub-sector mining companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with descriptive and verification methods. The study population consists of 10 iron and steel sub-sector mining companies listed on the Indonesia Stock Exchange. The sampling technique is purposive sampling based on criteria so that the number of samples becomes 9 companies. The independent variables in this study include liquidity as measured by the Current Ratio, profitability as measured by Return on Asset, and solvency as measured by the Debt to Equity Ratio. While the dependent variable is dividend policy as measured by the Dividend Payout Ratio. Data collection techniques are carried out through documentation studies and literature studies. Data analysis uses panel data regression with the help of Eviews 12 software. The results of the study indicate that liquidity (CR) does not have a significant effect on dividend policy. While profitability (ROA) and solvency (DER) have a significant effect on dividend policy. Simultaneously, the three independent variables have a significant effect on dividend policy with a determination coefficient of 61.54%, while the rest is influenced by other factors not examined in this study.